Professionals' Views and Experiences of Using Rehabilitation Robotics With Stroke Survivors: A Mixed Methods Survey - Lutong Li (Frontiers Media S.A., 2021)
Objective: To understand the reason for low implementation of clinical and home-based rehabilitation robots and their potential.Design: Online questionnaire (November 2020 and February 2021).Subjects: A total of 100 professionals in stroke rehabilitation area were involved (Physiotherapists n = 62, Occupation therapists n = 35).Interventions: Not applicable.Main Measures: Descriptive statistics and thematic content analysis were used to analyze the responses: 1. Participants' details, 2. Professionals' views and experience of using clinical rehabilitation robots, 3. Professionals' expectation and concerns of using home-based rehabilitation robots.Results: Of 100 responses, 37 had experience of rehabilitation robots. Professionals reported that patients enjoyed using them and they increased accessibility, autonomy, and convenience especially when used at home. The main emergent themes were: “aims and objectives for rehabilitation robotics,” “requirements” (functional, software, and safety), “cost,” “patient factors” (contraindications, cautions, and concerns), and “staff issues” (concerns and benefits). The main benefits of rehabilitation robots were that they provided greater choice for therapy, increased the amount/intensity of treatment, and greater motivation to practice. Professionals perceived logistical issues (ease of use, transport, and storage), cost and limited adaptability to patients' needs to be significant barriers to tier use, whilst acknowledging they can reduce staff workload to a certain extent.Conclusion: The main reported benefit of rehabilitation robots were they increased the amount of therapy and practice after stroke. Ease of use and adaptability are the key requirements. High cost and staffing resources were the main barriers.